3D Computational Sketch Synthesis Framework: Assisting Design Exploration Through Generating Variations of User Input Sketch and Interactive 3D Model Reconstruction. (March 2020) - Ban, Seonghoon; Hyun, Kyung Hoon
Abstract: A framework is proposed for facilitating the exploration process during the early design phase through computational sketch synthesis and interactive 3D reconstruction. In that phase, designers concentrate on developing concepts through numerous alternatives. Therefore, they constantly sketch so that they can rapidly visualize their ideas. Recently, the design industry has attempted to streamline the design process by implementing 3D model generation in the early design phase so that ideas may be more thoroughly explored, thus improving concept and final design conformance; however, efficiency issues have arisen. In this study, a 3D computational sketch synthesis framework was developed comprising two major components. First, a robust method was proposed to synthesize design alternatives by interpolating an input sketch with sketches in a database so that unvisited combinations may be explored. Secondly, a novel interactive 3D model reconstruction method was developed to facilitate the shape transition of design elements so that designers can quickly evaluate the potential of a large number of design variations. Finally, an interface for design refinement was developed so that designs may be embodied by sketching over the 3D model. To test the proposed methodology, expert designers were recruited for a validation experiment with two conditions followed up by in-depth interviews. In the first condition, the participants were asked to sketch based on a design brief in their current working manner. In the second condition, they were asked to create designs using the proposed framework. It was tested whether there was a difference in the design outcomes. It was demonstrated that the proposed framework resulted in more satisfactory and higher-quality designs and generated design alternatives faster and in greater quantities. All participants agreed that the framework could be useful in the early design phase and responded that the proposed system provides more design inspiration than traditional design methods. Most importantly, it was demonstrated that the proposed framework could enhance the reevaluation potential of design concepts and assist in making better-informed design decisions. Graphical abstract: Highlights: A framework is proposed to facilitate the design exploration process in the early design phase. Design alternatives are synthesized by interpolating an input sketch with sketches in the database. An interactive 3D reconstruction method is proposed to facilitate the shape transition of design elements. Experiments with experts are conducted to verify the proposed framework.